INSTRUCTIONAL LEADERSHIP, PROGRESSIVE PROFESSIONAL DEVELOPMENT, WORK MOTIVATION, AND THE ASSESSMENT RESULTS OF ELEMENTARY SCHOOL TEACHER COMPETENCY - Kristiani, Tutik; Suriansyah, Ahmad; Metroyadi (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this research is to describe and analyze the relationship between instructional leadership, progressive professional development, work motivation, and the results of elementary school teacher competency tests. The sample number of 120 was obtained by Proportional Random Sampling from 172 people in 22 schools at Binuang District. Data was collected using questionnaires that had passed validity and reliability tests. It was then analyzed by the product-moment correlation. The results obtained indicated a strong correlation between instructional leadership, continuing professional development, and work motivation about teacher competency test results. This research is expected to enhance teacher development and in further studies to improve education. Furthermore, it could be used by the teachers as an evaluation material, and as feedback for refinement and improvement of their ability and delivery. Also, information from this document could be used by the school principal to foster a good working environment for teachers. With good guidance, teachers would be competent enough to improve the learners? achievement. Additionally, this research provides the education stakeholders information which could be used in decision making to foster the teaching profession to achieve set goals and the quality of learning. And, it could be utilized as a reference document in future researches regarding the same subject matter.